Iowa Birdline update, February 6, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Email for the Iowa Birdline update for February 6, 1995. Highlights of the update include sightings of the continued presence of the Common Eider, Lesser Black-backed Gull and the Long-tailed Duck, a new highlight was the sighting of a Varied Thrush. Also included are handwritten notes for the next week's update with sightings of three Tundra Swans, a Greater Scaup and four Short-eared Owls. Epson - sheet feed/flatbed